Exploring the Importance and Presence of Maqāsid al-Sharī’ah in Islamic Banking Products and Services - Mohammad Qutaiba; Mohd Owais (Talaa : Journal of Islamic Finance, 2024)
This study explores the importance and presence of Maqāsid al-Sharī’ah in Islamic banking products and services, emphasizing their role in promoting justice, equity, and general welfare. While Islamic banking adheres to Shariah principles, such as the prohibition of riba and gharar, questions persist about the alignment of its products with the broader ethical objectives envisioned by Maqāsid al-Sharī’ah. These objectives, which include the preservation of religion, life, intellect, lineage, and wealth, aim to transform financial practices into instruments of socio-economic justice and communal well-being. The study critically examines whether Islamic banking products, such as Mudarabah and ijarah, genuinely uphold these principles or simply replicate conventional financial instruments under a Shariah-compliant framework. Drawing from academic literature, industry reports, and case studies, the research evaluates the design, implementation, and impact of key Islamic banking products to assess their alignment with Maqāsid al-Sharī’ah. It also highlights successes and areas for improvement within the industry, addressing concerns about the practical realization of ethical objectives in a competitive financial landscape. This paper underscores the necessity of integrating these higher objectives into financial practices. The findings contribute to a deeper understanding of how Islamic banking can serve as a true alternative to conventional systems, fostering holistic socio-economic progress and addressing global challenges such as poverty alleviation, wealth inequality, and environmental sustainability